2006
DOI: 10.1016/j.aquabot.2006.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The relation between geomorphological features and species richness in the low flow channel of the Warche, downstream from the Bütgenbach dam (Ardennes, Belgium)

Abstract: The Butgenbach dam, built on the Warche River (Ardennes, Belgium) in 1931 brought about two major changes: a significant reduction in the frequency and magnitude of the minimum discharges during the growing season (April-September) and the formation of numerous new geomorphological features (islets, pebble bars and rock outcrops) in the low flow channel. These changes have lead to an increase in the number of vascular plants downstream from the dam. Between 1994 and 1997, 74 species (bryophytes and phanerogams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Langlade and Decamps () and Assani et al . () observed litter accumulation is not favorable for plant growth as well as for diversity. This is due to the fact that litter can act as a barrier to sprouting plants and can be obvious in elevated habitats that are not subject to frequent water flow.…”
Section: Discussionsupporting
confidence: 90%
“…Langlade and Decamps () and Assani et al . () observed litter accumulation is not favorable for plant growth as well as for diversity. This is due to the fact that litter can act as a barrier to sprouting plants and can be obvious in elevated habitats that are not subject to frequent water flow.…”
Section: Discussionsupporting
confidence: 90%
“…The choice of the same morphological units, namely sand bars, is based on the fact that, in rivers, the inherent heterogeneity introduced by local topography can affect the effects of water level on the species abundance of sites [9]. Thus, [33] have shown that the number of species on islets located downstream from the Butgenbach dam on the Warche River (Belgium) was strongly influenced by the extent of erosion of these islets. Sediments samples (500 g) were collected on each bar at a depth of 15 cm from three sites along a longitudinal transect (from upstream to downstream).…”
Section: Measurement Of Abiotic and Biotic Variablesmentioning
confidence: 99%
“…Along the longitudinal gradients substrate types was the only factor significant negative correlation with species richness, Nilsson et al (1989) found substrate types and substrate heterogeneity were significant correla tion with species, and at the inter particle size and inter types the species richness reached the highest. Assani et al (2006) using CCA found that substrate types was signification with species, especially for the small particle (<2 mm) had the more signification, species number decreased following with the small ones content increasing. They thought that the small ones impeded the germination of seeds, so decreased the number of species, which was the same to our study.…”
Section: Spatial Pattern Along the Rivermentioning
confidence: 93%